Hybrid Renewable Energy System Design for Rural Areas in Western China - Yuan Xian; Jin Xiu (RUBINSTEIN, 2025)
This study aims to design and evaluate a hybrid renewable energy system for rural areas in Western China. The region, comprising provinces like Gansu, Ningxia, Qinghai, and Xinjiang, faces limited access to modern energy infrastructure, with many areas still relying on coal-based power generation. The potential for renewable energy is substantial, with abundant solar, wind, and hydro resources. The main objective of this research was to develop a hybrid system that integrates solar, wind, and hydro power to create a reliable and sustainable energy supply while reducing reliance on fossil fuels and lowering greenhouse gas emissions. Using a combination of Experimental Design and Simulation Methods, we developed several scenarios incorporating various renewable energy sources and battery storage systems. These systems were tested in representative rural areas, considering local weather conditions and energy resource availability. The findings show that the hybrid system can efficiently meet energy demands, with system efficiencies reaching up to 92%, reducing energy costs and contributing significantly to CO2 emission reductions. Economically, the initial investment for these systems is high, but operational costs are low compared to conventional coal-based generation. The payback period is estimated at 6-8 years, making it a feasible long term investment. Environmental impact analysis demonstrates a potential 70% reduction in CO2 emissions compared to fossil fuel based power generation. The study concludes with several policy recommendations, including fiscal incentives to reduce initial investment costs, development of energy distribution infrastructure, and the implementation of training programs for local communities to manage and maintain renewable energy systems. These measures are essential to support the widespread adoption of hybrid renewable energy systems in rural areas of Western China and can serve as a model for other developing countries facing similar challenges.